Pengaruh Media Augmented Reality Terhadap Pemahaman Konsep Siswa Kelas V Pada Materi Bangun Datar - Adnia Rianti Pradita; Nandang Budiman; Sardin Sardin (Journal on Education, 2024)
This study aims to analyze the impact of Augmented Reality (AR)-based learning media on students' conceptual understanding of flat shapes in elementary education. A quasi-experimental design with a non-equivalent group design approach was employed, involving two groups: an experimental group utilizing AR-based media and a control group employing conventional teaching methods. Data were collected through pre-tests and post-tests and analyzed using descriptive statistics, normality tests, homogeneity tests, paired sample t-tests, and independent sample t-tests. The findings indicate that AR-based media significantly enhance students' conceptual understanding, as evidenced by the higher post-test mean scores of the experimental group compared to the control group. AR media facilitates interactive content delivery and effective 3D visualization, boosting students' motivation and engagement. This study recommends further development of AR-based media for various learning subjects to support more innovative and digitally aligned teaching practices.